Phytochemical compositions and antioxidant activities of Malaysian stingless bee honey - Maringgal, Bernard; Hashim, Norhashila; Mohamed Amin Tawakkal, Intan Syafinaz; Tengku Muda Mohamed, Mahmud; Abdul Shukor, Nur Indah (Universiti Putra Malaysia Press, 2019)
The current study investigates the phytochemical composition of Malaysian stingless bee honey (Kelulut honey-KH), which consists of total phenolic (TPC) and total flavonoid content (TFC), and antioxidant activity. The honey was collected from five different regions in Malaysia i.e. south, central, eastern, northern and east coast regions. TPC and TFC were quantified by using Folin-Ciocalteu and the aluminum chloride colorimetric techniques, respectively. The antioxidant activity was investigated using two methods: 1) 1,1-diphenyl- 2-picrylhydrazyl (DPPH) radical scavenging assay; 2) ferric reducing/antioxidant power assay (FRAP). The findings indicated that there were significant differences in phytochemical compositions and antioxidant activities of KH between different regions. This implies that geographical location, as well as cultivation and treatment processes, have significant effects on the KH quality.